Assessment of novel hybrid treatment wetlands as nature-based solutions for pharmaceutical industry wastewater treatment - Al-Mashaqbeh, Othman; Alsalhi, Layal; Salaymeh, Lana; Lyu, Tao (Wiley, 2023)
This study investigated the use of nature-based solutions for treating real pharmaceutical industry wastewater in Jordan. A pilot-scale hybrid treatment wetland (TW) equipped with local zeolite was employed, comprising a tidal flow TW and a horizontal subsurface flow TW. This system was efficient in treating pharmaceutical wastewater with removal efficiencies of 61.4%, 52.6%, 60.1%, and 61.9% for chemical oxygen demand, total phosphorus, total nitrogen, and NH4+-N, respectively. The final effluent met Jordanian standards for the reuse of treated wastewater in irrigation (Class B). Five pharmaceuticals, namely, enrofloxacin, ciprofloxacin, ofloxacin, lincomycin, and trimethoprim, demonstrated nearly completed removal (93.6–99.9%). Moderated removal performances (59.2–68.2%) were observed for two compounds, flumequine and sulfaquinoxaline. However, three pharmaceuticals, namely, carbamazepine, diclofenac, and sulfadimidine, showed limited removal performances (1.1–20.5%). This study supported the feasibility of using nature-based solutions for treating pharmaceutical wastewater and highlighted that future studies are required to optimize this strategy for removing a broader range of pharmaceuticals.
Keywords: constructed wetlands; green technology; micropollutants; treatment wetlands; wastewater treatment